Craniofacial abnormality with skeletal dysplasia in mice lacking chondroitin sulfate N-acetylgalactosaminyltransferase-1. Issue 1 (December 2018) - Ida-Yonemochi, Hiroko; Morita, Wataru; Sugiura, Nobuo; Kawakami, Ryosuke; Morioka, Yuki; Takeuchi, Yuka; Sato, Toshiya; Shibata, Shunichi; Watanabe, Hideto; Imamura, Takeshi; Igarashi, Michihiro; Ohshima, Hayato; et al.
Abstract Chondroitin sulfate (CS) proteoglycan is a major component of the extracellular matrix and plays an important part in organogenesis. To elucidate the roles of CS for craniofacial development, we analyzed the craniofacial morphology in CSN -acetylgalactosaminyltransferase-1 (T1) gene knockout (KO) mice. T1KO mice showed the impaired intramembranous ossification in the skull, and the final skull shape of adult mice included a shorter face, higher and broader calvaria. Some of T1KO mice exhibited severe facial developmental defect, such as eye defects and cleft lip and palate, causing embryonic lethality. At the postnatal stages, T1KO mice with severely reduced CS amounts showed malocclusion, general skeletal dysplasia and skin hyperextension, closely resembling Ehlers-Danlos syndrome-like connective tissue disorders. The production of collagen type 1 was significantly downregulated in T1KO mice, and the deposition of CS-binding molecules, Wnt3a, was decreased with CS in extracellular matrices. The collagen fibers were irregular and aggregated, and connective tissues were dysorganized in the skin and calvaria of T1KO mice. These results suggest that CS regulates the shape of the craniofacial skeleton by modulating connective tissue organization and that the remarkable reduction of CS induces hypoplasia of intramembranous ossification and cartilage anomaly, resulting in skeletal dysplasia.